Creative Engagement by Wounded, Injured or Ill Australian Defence Force Personnel. - Grey, G. (Journal of Military & Veterans' Health, 2025)
While there has long been an extensive range of medical, pharmaceutical, psychological, physiological, spiritual and physical programs available to ADF personnel seeking health assistance, allied health practices-- particularly creative arts interventions--are still relatively new in the wellbeing context The Australian Defence Force Arts for Recovery, Resilience, Teamwork and Skills Program (hereafter, ADF ARRTS) is an immersive, non-clinical residential program of creative engagement, funded and delivered by the ADF It has been held biannually at the University of Canberra's ACT campus since 2015, delving into the disciplines of creative writing, music and rhythm, and visual arts and, for a time, drama The Defence Science and Technology Group assessed early programs for any improvements in the psychological wellbeing and recovery of Australian military personnel with service-related injuries, finding that, compared to baseline levels, there were significant improvements in self-reported self-esteem, social functioning, physical functioning and general positive affect, and significant reductions in psychological distress, insomnia and post-traumatic levels There was no significant change in negative affect levels 1 With very encouraging short-term results, as a people-focused program, it remained incumbent on qualitative research into the longer-term effectiveness of program attendance, and on how creative engagement modalities may act to offer improved outcomes for uniformed personnel and veterans The subsequent qualitative case study, reported here, clarifies the impacts, benefits, challenges and outputs of how engaging with creativity can shape identity and future directions for wounded, injured and ill person